2021
DOI: 10.1111/tri.13824
|View full text |Cite
|
Sign up to set email alerts
|

Considering extended right lobe grafts as major extended donor criteria in liver transplantation is justified

Abstract: Summary The outcomes of split‐liver transplantation are controversial. This study compared outcomes and morbidity after extended right lobe liver transplantation (ERLT) and whole liver transplantation (WLT) in adults. MEDLINE and Web of Science databases were searched systematically and unrestrictedly for studies on ERLT and its impact on graft and patient survival, and postoperative complications. Graft loss and patient mortality odds ratios (OR) and 95% confidence intervals (CI) were assessed by meta‐analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 55 publications
(207 reference statements)
1
19
0
Order By: Relevance
“…Based on these findings, we suggested that ERLT livers be considered maEDC grafts. (11) We hypothesized that the labMELD score, which reflects the patient's clinical condition and acuity, may determine the ERLT outcome, but we were not able to confirm this hypothesis because the included studies did not report recipient data. This emphasized that recipient parameters are neglected when it comes to addressing issues of a highly technical procedure and allocating organs for ERLT.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Based on these findings, we suggested that ERLT livers be considered maEDC grafts. (11) We hypothesized that the labMELD score, which reflects the patient's clinical condition and acuity, may determine the ERLT outcome, but we were not able to confirm this hypothesis because the included studies did not report recipient data. This emphasized that recipient parameters are neglected when it comes to addressing issues of a highly technical procedure and allocating organs for ERLT.…”
Section: Discussionmentioning
confidence: 91%
“…One way to avoid this bias and to remain within the optimal CIT range would be to improve logistics and to allocate ex situ split grafts to pediatric and adult transplantation candidates at the center where the ex situ split‐liver procedure is performed and to allocate in situ split grafts to different centers. ( 11 ) Combined with machine perfusion, this may abrogate the negative physiological consequences of prolonged ischemia time especially in ex situ ERLT. ( 20 ) Although information on splitting technique was not available in this study, the analysis revealed a CIT cut‐off of 10 hours, beyond which the outcomes of ERLT are suboptimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major extended donor criteria (maEDC) organs are a good alternative for patients with HCC who are in a better condition and have lower labMELD scores 9 , 96 . The studies included in the present analysis did not provide donor data, which means that an analysis of whether maEDC grafts or grafts with a higher donor risk index are suitable for patients who exceed the Milan criteria but meet the extended selection criteria was not possible 97 , 98 . This may be interesting, because while recurrence-free survival depends mostly on the recipient characteristics, overall survival may be also affected by donor and organ factors that are not considered by the selection models.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to ideal grafts, EDC organs are heterogeneous and are associated with higher risk of graft failure, which will unlikely decrease unless organ preservation is improved [7,8,65]. As relative risks for a specific liver allograft and recipient, the DRI, the ET-DRI, and the BAR scores have helped in allocating organs to specific recipients, but clear cutoff values have not yet been defined.…”
Section: Discussionmentioning
confidence: 99%